Vitamin D and respiratory health - David A. Hughes; Rosemary Norton (2009)
Summary Vitamin D is now known to be of physiological importance outside of bone health and calcium homeostasis, and there is mounting evidence that it plays a beneficial role in the prevention and/or treatment of a wide range of diseases. In this brief review the known effects of vitamin D on immune function are described in relation to respiratory health. Vitamin D appears capable of inhibiting pulmonary inflammatory responses while enhancing innate defence mechanisms against respiratory pathogens. Population-based studies showing an association between circulating vitamin D levels and lung function provide strong justification for randomized controlled clinical trials of vitamin D supplementation in patients with respiratory diseases to assess both efficacy and optimal dosage.